Microbial Count and AvBD10 Expressions in Ovaries and Oviducts of Kampung Unggul Balitbangtan (KUB)-1 Chickens Following Intravaginally CpG-ODN and S. Enteritidis - Suryohastari, Raden Rara Bhintarti; Sumarsono, Sony Heru; Giri-rachman, Ernawati Arifin; Edi, Suryo Purnomo; Sukoco, Rinto; Wicaksana, Dwi Nawang (Universitas Gadjah Mada, 2024)
Indonesia boasts diverse native chickens (Gallus gallus domesticus) known for more disease resistance in comparison to broiler chicken, and Kampung Unggul Balitbangtan (KUB)-1 is designated as Indonesia's superior breed. Salmonella Enteritidis (SE) is associated with salmonellosis, a foodborne illness that can be transmitted by transovarial, wherein colonisation in the oviduct ascends to the ovaries. However, studies mimicking transovarial salmonellosis via intravaginal treatment of chicken have been limited. Meanwhile, Cytosine-phosphate-guanine oligodeoxynucleotide (CpG-ODN) stimulation has been known to induce avian β-defensins (AvBDs). This in vivo study aimed to determine the effects of intravaginal CpG-ODN treatment and SE challenged on microbial count and AvBD10 expression regarding the potential of intravaginally CpG-ODN to enhance innate immunity as an alternative approach against transovarial Salmonellosis. A total of 39 KUB-1 chickens were divided into four groups: T1 (CpG-ODN treatment), T2 (SE treatment), T3 (CpG-ODN treatment + challenged with SE), and C (Control). Observation was carried out from day 1 to day 4 post-intravaginal (PI). We found a significant increase in ovarian microbial count (p≤0.05). Notably, ovaries and oviducts remained uncontaminated post-SE challenge. Intravaginal CpG-ODN treatment significantly upregulated AvBD10 in both ovaries (p=0.016) and oviducts (p=0.023). Therefore, KUB-1 chickens exhibit SE immunity, and intravaginal CpG-ODN administration holds promise for preventing transovarial Salmonellosis in laying hens.